CONTROLLING OF ORGANIZATIONAL CHANGES AT THE ENTERPRISE - M. Bobrova (Вестник университета, 2017)
Article is devoted to a complex research of economic category «controlling». The author gives the generalized characteristic of controlling as the methodology of management of changes containing a theoretical basis, focus, information streams, technology, structure and tools of decision-making. The hypothesis that application of different ways of controlling at management of activity of the enterprise gives the chance to it to develop the successful concept of adoption of administrative decisions directed to reduction of expenses and time of the organization, development, acceptance and implementation of administrative decisions is proved.